2023
DOI: 10.1037/xlm0001170
|View full text |Cite
|
Sign up to set email alerts
|

Truth by repetition … Without repetition: Testing the effect of instructed repetition on truth judgments.

Abstract: Past research indicates that people judge repeated statements as more true than new ones. An experiential consequence of repetition that may underly this "truth effect" is processing fluency: processing statements feels easier following their repetition. Here, we examine the effect of merely instructed (i.e., not experienced) repetition on truth judgments, which we compared to the effect of factual repetition. In two preregistered experiments (N=468), we found a larger truth effect for factual repetition compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
6
10
0
Order By: Relevance
“…In support of the role of beliefs, Mattavelli et al (2022) found a truth effect even when repetition was dissociated from experience; that is, when participants rated the truth value of statements that were merely told to be repeated vs. new (while not being actually repeated or not).…”
Section: The Truth Effectmentioning
confidence: 92%
See 1 more Smart Citation
“…In support of the role of beliefs, Mattavelli et al (2022) found a truth effect even when repetition was dissociated from experience; that is, when participants rated the truth value of statements that were merely told to be repeated vs. new (while not being actually repeated or not).…”
Section: The Truth Effectmentioning
confidence: 92%
“…One hundred and thirty participants (79 females, 51 males, Mage = 39.10, SDage = 11.54) were recruited via Prolific Academic and paid £ 0.63 for their participation. We applied five screening criteria: participants declaring to be English speakers, to live in the United States, have an approval rate of at least 95%, have at least 100 previous submissions on Prolific, and did not take part in previous related studies (Mattavelli et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that an affirmative tag makes the claim more believable and increases its memorability and retrievability, biasing the individual toward a "true" judgment. In a recent study, Mattavelli et al (2023) demonstrated that participants gave higher truthiness ratings for statements which were said to have been repeated for other participants than statements without alleged repetition. Hence, enhanced truthiness judgments could result from "merely instructed repetition" without the experience of repetition.…”
Section: Estimation Of Own Knowledge: a Sense Of Knowledgementioning
confidence: 99%
“…In line with previous research, we also predict that truth judgments are related to memory for statement repetition. Specifically, we predict (a) that the truth effect increases with better discrimination between old and new statements (e.g., Silva et al, 2017) and (b) that participants judge new statements that they think were repeated as more certainly true than new statements that they think were not repeated (e.g., Mattavelli et al, 2022). To test whether moral judgments rely on processes involved in assessing perceived truth-value, we compare the moral repetition effect and the truth effect and the relation of moral judgments and truth judgments to memory for statement repetition.…”
Section: Hypothesesmentioning
confidence: 99%
“…Referential memory networks presumably lead to higher fluency experiences and to remembering a statement. Yet, merely believing that one saw a statement beforethat was in fact not repeatedseems to increase the perceived truth of the statement, too (Mattavelli et al, 2022; see also Bacon, 1979). The perceived truth-value of a statement therefore seems to be informed by fluency but also by memory of a statement.…”
Section: Effects Of Repetition On Judgmentsmentioning
confidence: 99%